Concept Mapping:: A Tool for Improving Teaching, Learning, and Assessment in Landscape Architecture Design Studios - Powers, Matt; Hansen, Shea (ARCC Conference Repository, 2019)
Concept mapping is an educational tool with the capability of transforming teaching, learning, and assessment in design studios. A concept map is a graphic representation or diagram of knowledge that documents how effectively a learner organizes, represents, and understands a concept. Concept maps can be used by faculty members to assess their teaching efficacy and by students to assess their learning comprehension. Concept maps are particularly appropriate for design studios where project-based learning is common and students and faculty are familiar with creating and analyzing graphic representations. Studio teachers typically assess their students’ progress by critiquing drawings, models, and other graphic representations. However, this type of assessment corresponds to what students choose to show in their work and not the full range of what they’ve learned over the duration of the studio project. This means that teachers often measure improvements in performance and not necessarily changes in cognition. When combined with typical studio assessments, concept maps provide teachers with another layer of evaluative data that they can use to see what their students have and haven’t learned. In addition, concept mapping allows a student’s misunderstandings to emerge, indicating the need for an instructional intervention or a reevaluation of teaching methods. This paper uses emergent findings from an ongoing study to support the usefulness of concept maps as an alternative assessment method in landscape architecture design studios.